ELAZIĞ İL MERKEZİ YERLEŞİM ALANININ DEPREMSELLİĞİ - PALUTOĞLU, MAHMUT (Fırat Üniveristesi, 2005)
In this study, approximate 300000 persons of Elazag city centrum that investigation of ground was purposed of earthquake risk as detailed to bring up. The investigation area was prepared the cropping out formations units have separate and geological map of scale 1/5000 and cross sectiortElazig become center 50, 100 ve 150 kilometer for radius areas were maked seismic risk analysis. This analysis, Gutenberg-Richier ve Gumbeli were maked relations used. Earthquake analysis in chapter nine senario of earthquake was determined in the study area will be occured seismicsjty parameters. The geotecnic investgation was determined that grounds earthquake instantly behavior. According to liquefy probability S velocity wave. Seperately was prepared micro- zonafion and ground quefy probability to become two number map. KEY WORDS; Elazığ, earthquake risk, seismic risk. XIV
Seismicity of Elazığ city center settlement area
Bu tezin, veri tabanı üzerinden yayınlanma izni bulunmamaktadır. Yayınlanma izni olmayan tezlerin basılı kopyalarına Üniversite kütüphaneniz aracılığıyla (TÜBESS üzerinden) erişebilirsiniz.
Keywords: Jeoloji Mühendisliği